Adoption of Mobile Health Applications Among Adults in Kulai, Johor - See, Lee Yen; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2021)
In what way of usage level and practicality of mobile health applications (m-health apps) to support healthy lifestyle among Malaysian is unclear. So, the purpose of this research is to identify the factors towards adoption of m-Health apps and to determine the relationship between the factors and the adoption of m-Health apps among adults(age of 20 to 60 years old)  in Kulai, Johor. The factors that being studied were relative advantage, perceived ease of use, compatibility, observability, trialability and perceived risk. This study was cross-sectional study using structured questionnaire as survey instrument and employed convenient sampling techniques. Based on population in Kulai, Johor, the expected number of samples was 383 respondents. Later, the total number of 245 sets of online questionnaires form had been distributed and the rate of response was 63.97%. Descriptive analysis using SPSS was used to analyzed the data from the questionnaire. The finding of this research identified factors towards intention of using m-Health apps and relationship between the factors and usage of m-Health apps. This research may contribute some insights to m-Health apps software developer to improve their apps, so that it is easy-to-use and more user friendly.